2008
DOI: 10.1016/j.nbd.2008.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Src kinase inhibition decreases thrombin-induced injury and cell cycle re-entry in striatal neurons

Abstract: Since Src kinase inhibitors decrease brain injury produced by intracerebral hemorrhage (ICH) and thrombin is activated following ICH, this study determined whether Src kinase inhibitors decrease thrombin induced brain injury. Thrombin injections into adult rat striatum produced focal infarction and motor deficits. The Src kinase inhibitor PP2 decreased thrombin-induced Src activation, infarction in striatum and motor deficits in vivo. Thrombin applied to cultured post-mitotic striatal neurons caused: injury to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 46 publications
(59 reference statements)
1
55
0
Order By: Relevance
“…Left and right swings were recorded by a blinded observer over 45 seconds and the percentage of left swings was calculated. A right striatal lesion produces a leftward swinging bias (Liu et al, 2008). …”
Section: Methodsmentioning
confidence: 99%
“…Left and right swings were recorded by a blinded observer over 45 seconds and the percentage of left swings was calculated. A right striatal lesion produces a leftward swinging bias (Liu et al, 2008). …”
Section: Methodsmentioning
confidence: 99%
“…from Ischemic Stroke-Although Src inhibitors can reduce stroke-induced brain damage in rodent models (16,17,54), their use may adversely affect the recovery of brain cells from the damage. Relevant to this, Takadera et al (19) demonstrated that treatment with Src kinase inhibitors induces apoptosis in cultured cortical neurons.…”
Section: Prevention Of Calpain-mediated Cleavage Of Src As a Therapeumentioning
confidence: 99%
“…Mature neurons (MNs) were prepared from combined embryonic day 18 rat brain tissue as previously reported with minor modification (Liu et al, 2008). Briefly, tissue was triturated ten times to break up the brain tissue in 1 ml Hibernate medium (BrainBits, Springfield, IL) containing 2% B27.…”
Section: Cultures Of Rat Mature Neuronsmentioning
confidence: 99%